Effect on quality of life and psychosocial issues of patients with maxillofacial fractures in rural setting - Laxmi Sureshkumar; Pankaj Patil; Yamuna Iyer (Wolters Kluwer Medknow Publications, 2021)
Background: Maxillofacial injuries are a serious public health problem and are often associated with severe morbidity, disfigurement, and psychological problems. The life of the patient often takes a turn for the worst and he/she has to face many difficulties moving forward. Analysing and determining the quality of life of such cases will give us a better understanding and insight and will further improve the care and treatment of the patients. Aims: Analyse and evaluate the psychosocial impact of maxillofacial fractures on individuals who were healthy pre-trauma. Material and Methods: The participants are the 30 patients with facial trauma reported to the Department of Oral and maxillofacial surgery of the School of Dental Sciences and Krishna hospital, Karad, who will be required to undergo surgical treatment (i.e., Open reduction and internal fixation for facial fractures) and are willing to participate in this study. All 30 patients were given a questionnaire form modified from the pre-existing Acute Stress Disorder Scale, Oral Health Impact Profile questionnaire and Posttraumatic Diagnostic Scale, which includes questions regarding speech, sense of taste, pain, uncomfortable eating, orientation, tension, unsatisfactory diet, interrupted meals, difficulty to relax, embarrassment, irritability, occupational dysfunction, etc. during their 15 days follow up appointment post-surgery. This obtained data was then analysed and was subjected to appropriate statistical analysis. Result: In a study sample of 30 patients, 8% were found with intense psychosocial issues due to trauma, 14% had a moderate, and 18% had mild issues that affected the quality of their life post-trauma. Conclusion: The study shows a great need for psychological screening and evaluation of patients with maxillofacial injury/fractures due to trauma to improve the patient's physical and psychological recovery.